Stories of a Collection - Bismuth, Pierre; Defeyt, Antpoine; de Failly, Laurence; Petre, Anne; Sorokina, Elena; Swinnen, Johan; ten Brink, Sanne; Wassenberg, Astrid; Wollaert, Raf (Brussels : ING, 2019)
Bunshaft, Gordon ; Alechinsky, Pierre ; Rauschenberg, Robert ; Pepper, Beverly ; Buren, Daniel ; Boltanski, Christian ; Gursky, Andreas ; Charlton, Allan ; François, Michel ; Gormley, Antony ; Horn, Roni ; Crewdson, Gregory ; Hatoum, Mona et al.
Love. Hate. Debate. Start a conversation with the ING Collection, ING Art Center, Brussels, 23.10.2019 - 15.03.2020
Book + 2 visitor's guide (eng, fre)
boek